Independent infinitives in discourse: towards a pragmatic typology - Palmerini, Monica (Círculo de Lingüística Aplicada a la Comunicación, 2018)
The aim of this article is to propose a new analysis and classification of the independent infinitive constructions in Spanish, based on discourse-pragmatic criteria (see Palmerini, 2007, 2012; Palmerini & Calò, en prensa). A review of the literature dedicated to the analysis, from different perspectives, of these special uses (Skydsgaard, 1977; Arjona-Luna Trail, 1980; Hernanz, 1999; RAE, 2009; Pérez Vázquez & Telli, 2012a; Quintero Ramírez, 2013a, 2014a, 2018) where the non-finite form of the infinitive behaves like an ‘independent’ verbal predicate, thus resembling the typical functioning of the finite verb, shows the lack of a theoretical approach focusing on the dimension of the use of these constructions in discourse while trying, at the same time, to offer a systematic account of the whole system of the spanish independent infinitives. To reach this double objective we base our analysis on four fundamental criteria (predicative force, type of speech act, discourse context, discourse functions) which allow us to sketch a tentative discoursepragmatic map of the independent infinitives’ system, that implies a revision of the traditional classification of these constructions. After distinguishing between predicative and non-predicative uses, our analysis identifies four kinds of speech act (assertive, performative, expressive, directive) realized by means of these grammatical resources, and recognizes different discourse specializations associated with the appearance of these structures in discourse (to enunciate, to narrate, to explain, to share experiences, etc.). This taxonomy highlights, among other things, two areas of innovation and expansion in the use of the independent infinitive in Spanish (cfr. Palmerini & Calò, en prensa): namely, the case of the enunciative infinitive (with performative value), and the expressive use developed in the communication through social networks.
Keywords: Spanish independent infinitive; discourse-pragmatic typology; speech acts; discourse functions.